MEMPOSISIKAN MASYARAKAT SEBAGAI GARDA DEPAN PELESTARI SUMBER DAYA ARKEOLOGI - Wasita, nfn (Naditira Widya, 2007)
Indonesian archaeologists are challenged by the huge number of cultural heritage that to be conserved. Concerning with this, the involvement of people surrounding the heritage places, as one of instrument of conservation, is very important. However, innovation in method and strategy to increase the people awareness in any conservation activities are still to be done.